2016
DOI: 10.1007/s40979-016-0011-0
|View full text |Cite
|
Sign up to set email alerts
|

Role-playing institutional academic integrity policy-making: using researched perspectives to develop pedagogy

Abstract: This article describes research-based role-play on academic integrity. In the role-play, doctoral students negotiated the revision of an institutional integrity policy representing different groups of academics and students. On the one hand, role-play as a teaching method and learning activity demonstrated the difficulty of accommodating different perspectives; on the other, it showed the power and necessity of negotiation in matters that involve value judgments. The role-play is described in detail along with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
0
8
0
2
Order By: Relevance
“…Academic integrity policy seems effective when it is a formal process rather than a case-by-case method (Winters Spain and Robles 2011) and coherent with the variety of initiatives that are undertaken in a university, without any leeway (Kolb et al 2015). In addition to this, it is implied that academic integrity policy would be more effective if developed by those to whom it is supposed to be applied, so it would be better accepted and respected (Löfström 2016;Richards et al 2016).…”
Section: Academic Integrity Policymentioning
confidence: 99%
“…Academic integrity policy seems effective when it is a formal process rather than a case-by-case method (Winters Spain and Robles 2011) and coherent with the variety of initiatives that are undertaken in a university, without any leeway (Kolb et al 2015). In addition to this, it is implied that academic integrity policy would be more effective if developed by those to whom it is supposed to be applied, so it would be better accepted and respected (Löfström 2016;Richards et al 2016).…”
Section: Academic Integrity Policymentioning
confidence: 99%
“…The P2ILC programme aligns with numerous studies, which document that role play increases classroom participation, reflexive and creative thinking, application of concepts, emotional engagement, and personal accountability (Löfström 2016;Grose-Fifer 2017;McCarthy and Anderson 2000;Poorman 2002;McWilliams and Nahavandi 2006;Poling and Hupp 2009). Studies have shown that specific exercises promote perspective-taking (Löfström 2012), and simulation (Wright-Maley 2015) and role play (Rosnow 1990;Strohmetz and Skleder 1992) help raise awareness of complexities in ethics; all of these are found in the programme.…”
Section: The P2lic Programmementioning
confidence: 86%
“…Although short workshops and tutorials can result in behaviour change, efforts to increase students' knowledge and skills as they relate to academic integrity are likely to result in greater success for students over the long term if practice or hands-on experiences are included in the teaching approach. Face-to-face lectures and e-learning tutorials can be similarly effective when the teaching strategies implemented are suitable to deliver the content (Clark, 1994) and encourage deep understanding (Löfström, 2016). Thus, the effectiveness of an educational intervention to promote academic integrity depends on the instructional methods utilized, and environmental and individual factors on students' perceptions, learning outcomes, and behaviors.…”
Section: Discussionmentioning
confidence: 99%